COMPARISON OF THE EFFECTIVINESES OF COOPERATIVE LEARNING MODEL BETWEEN TPS-NHT TYPE AND TPS-TGT TYPE IN MATHEMATICS LEARNING IN CLASS VIII AT SMPN 1 MAKASSAR - Andi Aras (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2016)
The study is experiment research which aims at: (1) describing the effectiveness of cooperative learning model of TPS-NHT type in Mathematics learning in classVIII at SMPN 1 in Makassar; (2) describing the effectiveness of cooperative learning model of TPS-TGT type in Mathematics learning in classVIII at SMPN 1 in Makassar; (3) discovering the comparison of the effectiveness of cooperative learning model between TPS-NHT type and TPS-TGT type in Mathematics learning in class VIII at SMPN 1 in Makassar. The population of the research was all of class VIII students at SMPN 1 in Makassar of academic year 2016/2017 and the samples consisted of two classes, namely class VIII.4 taught by cooperative learning model of TPS-NHT type and class VIII.5 taught by cooperative learning model of TPS-TGT type taken by employing cluster random sampling technique. The data which were collected consist of the students’ learning results, the students’ learning motivations, the students’ activities during the learning process and the students’ responses toward the implementation of learning model. The results of the research reveal that the score of Mathematics learning result of class VIII.4 students is in high category with the mean 83.85 and standard deviation 11.51, classical completeness is 85%, the average of normalized gain is in high category, the average score of students’ learning motivation is in high category, the average of normalized gain of learning motivation is ini medium category, the students’ activity in following the learning process is ini good category, and the students’responses toward the implementation of cooperative learning model of TPS-NHT type is positive. In general, it can be concluded that cooperative learning model of TPS-NHT type is effective to be implemented in Mathematics learning in class VIII.4 at SMPN 1 in Makassar. The score of Mathematics learning result of class VIII.5 students’is in high category with the mean 80.15 and standard deviation 9.79, classical completeness is 82.5%, the average of normalized gain is in high category, the average score of the students’ learning motivation is in high category, the average of normalized gain of learning motivation is in medium category, the students’ activity in following the learning process is in good category, and the students’ responses toward the implementation of cooperative learning model of TPS-TGT type is positive. In general, it can be concluded that cooperative learning model of TPS-TGT type is effective to be implemented in Mathematics learning in class VIII.5 at SMPN 1 in Makassar. The result of hypothesis test at the significant level α = 0.05 with t-test shows that H0 is accepted meaning that there is no difference of learning effectiveness between the students’ who were taught by using cooperative model of TPS-NHT type and the students’ who were taught by using cooperative model TPS-TGT type in Mathematics learning on SPLDV material in class VIII at SMPN 1 in Makassar